1985
DOI: 10.1152/jappl.1985.59.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill vs. floor walking: kinematics, electromyogram, and heart rate

Abstract: To identify the degree of difference between treadmill and floor walking, kinematic, electromyographic (EMG), and heart rate measurements were recorded in seven normal female subjects during walking at three speeds on the treadmill and on the floor. During treadmill walking, subjects tended to use a faster cadence and shorter stride length than during floor walking. In addition the displacements of the head, hip, and ankle in the sagittal plane showed statistically significant differences between floor and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
146
5
6

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(179 citation statements)
references
References 0 publications
20
146
5
6
Order By: Relevance
“…This may have affected our results to some extent but the differences are likely to be very small. Indeed, the limited number of EMG studies that have compared treadmill walking and floor walking failed to show clear differences in the underlying patterns of muscle activity, other than minor changes in the amplitude of muscle activity [16,17]. While these studies did not extend to the very low speed range it is unlikely that major differences would appear.…”
Section: Discussionmentioning
confidence: 99%
“…This may have affected our results to some extent but the differences are likely to be very small. Indeed, the limited number of EMG studies that have compared treadmill walking and floor walking failed to show clear differences in the underlying patterns of muscle activity, other than minor changes in the amplitude of muscle activity [16,17]. While these studies did not extend to the very low speed range it is unlikely that major differences would appear.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern can adapt easily to different speeds, 15,17 inclines, [30][31] surfaces such as overground versus treadmill [32][33][34][35] and uneven surfaces. 36 The main objective of the present study was to measure how SCI subjects adapt to changes in the walking speed.…”
Section: Discussionmentioning
confidence: 99%
“…While Ralston [39] reports that TJ and floor walking are metabolically the same, no consensus exists with regard to whether the results from treadmill walking accurately represent overground walking. Some studies reported that walking on a treadmill versus a floor differ kinematically [40] and metabolically [41,42]. The current study is a comparison between SJT and TJ with different floor conditions, and TJ may not be synonymous with jogging on the floor (slow jogging).…”
Section: Discussionmentioning
confidence: 89%